2019
DOI: 10.1186/s10194-019-1055-3
|View full text |Cite
|
Sign up to set email alerts
|

C-fibers may modulate adjacent Aδ-fibers through axon-axon CGRP signaling at nodes of Ranvier in the trigeminal system

Abstract: Background: Monoclonal antibodies (mAbs) towards CGRP or the CGRP receptor show good prophylactic antimigraine efficacy. However, their site of action is still elusive. Due to lack of passage of mAbs across the bloodbrain barrier the trigeminal system has been suggested a possible site of action because it lacks blood-brain barrier and hence is available to circulating molecules. The trigeminal ganglion (TG) harbors two types of neurons; half of which store CGRP and the rest that express CGRP receptor elements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
85
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(96 citation statements)
references
References 50 publications
7
85
1
1
Order By: Relevance
“…They may be activated by CGRP released from central terminals of other trigeminal afferents to facilitate neurotransmitter release and synaptic transmission (Takhshid et al 2007). Similarly, a recent immunohistochemical study identified CGRP receptor subunits at nodes of Ranvier of Aδ fibers adjacent to CGRP-containing C fibers in the ganglia and dura (Edvinsson et al 2019). Thus, there is a possibility of cross-talk between adjacent fibers as well in cell bodies in the ganglia.…”
Section: Significance Of Intraganglionic Cross-talk For Nociceptive Tmentioning
confidence: 96%
“…They may be activated by CGRP released from central terminals of other trigeminal afferents to facilitate neurotransmitter release and synaptic transmission (Takhshid et al 2007). Similarly, a recent immunohistochemical study identified CGRP receptor subunits at nodes of Ranvier of Aδ fibers adjacent to CGRP-containing C fibers in the ganglia and dura (Edvinsson et al 2019). Thus, there is a possibility of cross-talk between adjacent fibers as well in cell bodies in the ganglia.…”
Section: Significance Of Intraganglionic Cross-talk For Nociceptive Tmentioning
confidence: 96%
“…Presynaptic terminals in nerves that produce CGRP, take the form of focal swellings, occurring at regular intervals along the axon [23]. This mechanism may occur at the molecular level via axon-axon modulation of the two types of sensory fibers [78]. The C-fibers may modulate adjacent Aδ-fibers through axon-axon CGRP signaling at nodes of Ranvier in the trigeminal system.…”
Section: Cgrp Functionmentioning
confidence: 99%
“…As all these molecules are produced in the cell body, every mechanism interacting with their gene expression has consequences for the peripheral and central functions of these neurons. For example, CGRP receptors integrated into the presynaptic membrane of central trigeminal terminals may be activated by CGRP released from adjacent terminals of other trigeminal afferents to facilitate neurotransmitter release and synaptic transmission [67,68]. Another example is BDNF, the expression of which is enhanced by CGRP in cultured trigeminal neurons [69].…”
Section: Functional Significance Of Mediator Trafficking To Afferentmentioning
confidence: 99%